A Computational Model for Heat Transfer Coefficient Estimation in Electric Arc Furnace. Issue 3 (7th September 2015) - Logar, Vito; Fathi, Amirhossein; Škrjanc, Igor
Abstract : The paper studies the effects of solid and liquid steel properties on the heat transfer coefficient (HTC) in electric arc furnaces (EAFs). Mathematically speaking, the HTC is a function of solid and liquid steel properties. Different velocities of the bath cause different flow paths around the solid particles and therefore different HTCs—a computational issue that has not been addressed yet. Therefore, a simplified calculation model is proposed, intended for HTC estimation according to the EAF conditions. Although many studies investigated this topic, most of them either assume unconventional conditions for the EAF operation, are computationally complex or focus on a specific case; and are, therefore, hard to implement in general EAF models. The algorithm proposed in this paper introduces simplified, yet accurate equations for calculating the HTC between solid and liquid steels as a function of their properties. Due to simplicity of the algorithm, the computational times are very short; thus, the procedure can be used in online model environments in order to perform different heat‐transfer‐related calculations. The obtained results show high similarity with other practical and theoretical studies. Furthermore, implementation of the HTC calculation submodule in a comprehensive EAF model yielded high accuracy in steel‐bath temperature prediction. Abstract : Accurate, computationally fast, and mathematically simple estimation of the heat transfer coefficient between solid and liquid steels in electric arc furnace according to steel bath temperature, steel bath velocity, solid steel density and solid steel dimensions.